A Hybrid Structured Multistage Wiener Filter for GPS Interference Suppression - Qing-Dong Huang; Guang-Yue Lu; Zhi-Qiang Bao; Yong-Zhi Zhai; Sheng-Li Pang (Institute of Advanced Engineering and Science, 2013)
To suppress the influence of impulsive noise spikes (outliers) from the direction of arrival of the desired GPS signals, a combination of the Householder multistage Wiener filter (HMSWF) and the recently introduced Minimum Module Cascaded Canceller (MMCC) is employed to compose a hybrid structured HMSWF (HS-HMSWF) method. The enhanced algorithm is employed by space-time anti-jamming processing in GPS receiver, with the ability of natural protection against the impulsive noise spikes influence of weights calculation. In space signal processing, it can avoid the zero pitch formed at the direction of target signal, and prevent the desired signal be diminished. Simulation results demonstrated the favorable anti-jamming performance of the proposed algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3556